The effects of anxiety symptoms on postural stability in young adults - Matos, Paula (2022)
Anxiety is defined as a state or an emotional response. When excessive or prolonged may be reflected in thinking, behavior and motor skills, such as postural stability. To compare the population with and without anxiety symptoms in relation to postural stability on orthostatic position.